P638 Effectiveness and safety of risankizumab induction therapy for 100 patients with Crohn's disease: a GETAID multicentre cohort study. (30th January 2023) - Fumery, M; Defrance, A; Roblin, X; Altwegg, R; Caron, B; Hebuterne, X; Carmen, S; Meyer, A; Nachury, M; Laharie, D; Nancey, S; Le Berre, C; et al.
Abstract: Background: Phase III trials have demonstrated the efficacy of risankizumab in moderate-to-severe Crohn's disease (CD), but no real-world data are currently available. We aimed to assess the short-term effectiveness and safety of risankizumab in patients with CD. Methods: From May 2021 to May 2022, all patients with refractory luminal CD treated with risankizumab in 22 French GETAID centers were retrospectively included. The primary endpoint was steroid-free clinical remission at week 12 (Harvey-Bradshaw (HB) score < 5). Secondary endpoints included clinical response (≥ 3-point decrease of HB score and/or (HB) score < 5), biological remission (CRP ≤ 5 mg/L), need for CD-related surgery, and adverse events. Results: Among the 100 patients included, all have been previously exposed to anti-TNF agents, 94 to vedolizumab, 98 to ustekinumab (all exposed to at least three biologics) and 61 had previous intestinal resection. All but three (97%) received a 600 mg risankizumab intravenous induction at weeks 0-4-8. At week 12, steroid-free clinical remission was observed in 45.8% of patients, clinical remission in 58% and clinical response in 78.5%. Absence/mild abdominal pain with normal stool frequency was noted in 50% of patients at week 12. Biological remission was observed in 50% of patients. Six patients discontinued risankizumab before the week 12 visit due to lack of efficacy. CD-related hospitalization was needed in six patients, and three underwent intestinal resection. In multivariable analysis, only a history of ustekinumab loss of response ( vs primary failure) (Odds Ratio (OR), 2.80 ; 95%CI, 1.07 – 7.82; p=0.041) was significantly associated with clinical remission at week 12. Twenty adverse events (AE) occurred in 20 patients including 7 serious AE corresponding to 6 CD exacerbation and one severe hypertension. Conclusion: In a cohort of highly refractory patients with luminal CD and multiple prior drug failures including ustekinumab, risankizumab induction provided clinical response in about 3 out of 4 patients and steroid-free clinical remission in about half of patients.